Urban issue reporting applications towards government 2.0 - Soares, J.; Coutinho, C. (ISMSIT 2024 - 8th International Symposium on Multidisciplinary Studies and Innovative Technologies, Proceedings, 2024)
This study examines the role of civic technology within the Government 2.0 framework in addressing urban challenges, focusing on N a Minha Rua LX, a citizen reporting application in Lisbon. Using a mixed-methods approach combining qualitative comparative analysis with case studies, the research evaluates Na Minha Rua LX alongside SeeClickFix, My City Report, and FixMyStreet. Data from official websites, academic literature, and user feedback were analysed through systematic coding and thematic analysis. Findings indicate that while Na Minha Rua LX effectively facilitates issue reporting and tracking, it lacks advanced features present in other applications. The study explores how integrating CitymisVis, a data visualization tool, could enhance Na Minha Rua LX's functionality. The research concludes that realizing the full potential of such platforms in urban governance requires ongoing evaluation, development, and integration into broader urban management strategies.